Hubungan Anemia Ibu Hamil Dengan Kejadian Stunting Pada Balita Usia 6-23 Bulan di Tuban - Novita Mahera Putri (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Stunting is a nutritional problem that occurs if the HA is at a z-score of less than -2 elementary school which can result in linear growth disorders in toddlers. One of the risk factors that affect the incidence of stunting in toddlers is the nutritional status of the mother during pregnancy. Anemia in the mother during pregnancy is one of the nutritional problems that contribute to this. This study aims to analyze the relationship between the incidence of stunting in toddlers in Tuban and maternal anemia during pregnancy. This study uses a case control design and is retrospective. This study used a sample of 68 respondents divided into two groups selected using a systematic random sampling technique from mothers under five spread across Plumpang village. Primary data collection was carried out by conducting anthropometric measurements in the form of body length of toddlers and interviews with questionnaire guidelines to mothers of toddlers. The KIA book and stunting data from the Plumpang Health Center are needed to find out information on the history of anemia of pregnant women and the birth weight of toddlers. Data analysis using the Chi-Square test. According to the results of statistical tests, the variables of anemia and stunting incidence in toddlers in Tuban have a significant correlation (P-value = 0.016). The existence of a significant relationship between maternal nutritional status during pregnancy and the incidence of stunting in toddlers can be an important component of the formation and development of nutrition monitoring programs for pregnant women